TREATMENT OUTCOMES OF NEOADJUVANT PACLITAXEL-CARBOPLATIN CHEMOTHERAPY IN PATIENTS WITH STAGE III-IV EPITHELIAL OVARIAN CANCER AT NGHE AN ONCOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics and evaluate treatment response in patients with stage III-IV epithelial ovarian cancer who received neoadjuvant Paclitaxel-Carboplatin chemotherapy at Nghe An Oncology Hospital.Methods: This retrospective descriptive study included 50 patients with stage III–IV epithelial ovarian cancer who underwent neoadjuvant chemotherapy with the paclitaxel–carboplatin regimen at Nghe An Oncology Hospital between January 2020 and June 2026.Results: The mean age of the patients was 58 ± 7 years. Ascites was the most common clinical manifestation, occurring in 82% of cases. Most tumors measured ≥5 cm (80%), and high-grade serous carcinoma was the predominant histological subtype (64%). Serum CA125 levels exceeded 1,000 U/mL in 52% of patients. Stage IIIC and stage IV disease accounted for 58% and 42% of cases, respectively. The overall clinical response rate was 96%, including partial response in 84% and complete response in six patients (12%). Optimal cytoreductive surgery was achieved in 94% of patients. Histological subtype was significantly associated with clinical response to the regimen (p < 0.05).Conclusion:  Neoadjuvant chemotherapy with the paclitaxel–carboplatin regimen was associated with an objective response rate of 96% and an optimal cytoreductive surgery rate of 94% in patients with advanced-stage (FIGO III–IV) epithelial ovarian cancer who were not candidates for upfront surgery.
Keywords: epithelial ovarian cancer; neoadjuvant chemotherapy; Nghe An Oncology hospital